PERLAKUAN AKUNTANSI ASET TETAP SESUAI DENGAN PSAK PADA PT INKO JAVA SEMARANG TAHUN 2016 - Ririh Ayu Widyastuti; Christina Retno Gayatrie; Suko Suko Raharjo (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2019)
Fixed Asset plays an important role in the sustainability of a business. The purpose of this research is to analyze the suitability of accounting treatment of Fixed Assets from recognition to presentation in the financial statements applied by PT Inko Java with PSAK. Data collection methods used were interview, observation and literature study. The results of the research show that PT Inko Java in recognition, measurement at the time of acquisition and termination of Fixed Assets is according to PSAK but cost measurement after the acquisition and depreciation of Fixed Assets has not been appropriate so that the presentation in the financial statements is less appropriate to the actual situation. This research is presented with description method to describe PT Inko Java's overview and exposition method to explain the accounting analysis of Fixed Assets